The Analysis of Figurative Language in Tulus Song - Nessa Amalia; Dohra Fitrisia; Tengku Maya Silviyanti (Research in English and Education Journal, 2021)
This study discusses the analysis of figurative language in Tulus’ songs. The purpose of this research to determine the types of the figurative language contained in the songs. The researcher focuses on the most dominant figurative language. The source is taken from ten Tulus’ song that the title is Sewindu, Sepatu, Teman Hidup, Gajah, Jangan Cintai Aku Apa Adanya, Manusia Kua, Ruang Rindu, Langit Abu-abu, Monokrom, 1000 Tahun lamanya. The research design used in this research is qualitative, research with document analysis as a data collection technique based on Miles, Huberman, Saldana (2014). From the analysis that has been done, it was found 62 figurative languages contained in the ten songs selected in the Tulus’ songs. The figurative language found in this study is categorized based on the Perrine (in Arp, 2012). The data found were hyperbola (17 data), personification (13 data), symbol ( 10 data), simile (7 data), metaphor (5 data), metonymy (5 data), irony (2 data), allegory (1datum), paradox (1 datum), synecdoche, apostrophe, and litotes were not found in the ten of Tulus songs.